2008
DOI: 10.1007/s10195-008-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Late collapse of distal radius fractures after K-wire removal: is it significant?

Abstract: BackgroundThe aim of this study was to find out whether distal radius fractures treated by Kirschner wire (K wire) fixation loose reduction after wire removal and analyze the variables may influence this.Materials and methodsPatients who underwent K wire fixation for unstable fractures of distal radius over a period of 3 years were included in this retrospective study. Fractures were classified according to AO classification. Radiographs taken just prior to removal of K wires and radiographs taken at least 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The fractures were reduced and stabilized under the same anesthesia. Kurup, et al studied the late collapse of distal radius fractures after K-wire removal and its significance [ 26 ]. They found that the fractures did not suffer significant loss of reduction after removal of wires.…”
Section: Discussionmentioning
confidence: 99%
“…The fractures were reduced and stabilized under the same anesthesia. Kurup, et al studied the late collapse of distal radius fractures after K-wire removal and its significance [ 26 ]. They found that the fractures did not suffer significant loss of reduction after removal of wires.…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies by "Kreder" et al, "Fuji" et al, "Kurup" et al, "Mardanikivi" et al claim that distal end radius fractures, even when displaced, have better functional outcome with closed reduction and K-wire pinning compared to closed reduction and cast. 10,11,12,13 "Rosenthal" et al study found intrafocal pinning technique to be better compared to closed reduction and cast.…”
Section: Discussionmentioning
confidence: 99%
“…Anahtar kelimeler: radius kırıkları; giderler ve maliyet analizi; kemik vidaları after simple injuries and cause a significant amount of resource consumption in respect to health care costs as well as creating serious health problems 3 . In clinical trials, functional outcomes have been reported to be better after stable fixators which providing anatomical joint alignment and allowing early mobilization [4][5][6] . However, in some studies, it has been reported that anatomic alignment is not always sufficient to achieve satisfactory clinical outcome, good functional outcomes are achieved in some patients who anatomic alignment can not be provided 7,8 .…”
Section: Sonuç: Her Iki Grup Arasında Anatomik Ve Fonksiyonel Sonuçlar Açısından Anlamlı Bir Fark Elde Edilmemesine Karşın Perkütan çIvilmentioning
confidence: 99%